Enlightenment as Phenomenological Deconstruction - Voskanyan, Ashot (Bulletin of Yerevan University E: Philosophy, Psychology, 2014)
The impact of the idea of the “presence of spirit”, which is used as terminus technicus within the mentalist paradigm of Hegel-Heideggerian phenomenology can be represented in the linguistic-pragmatic language of postmodern philosophy by specific heuristic constructions like “conceptual personage” (G. Deleuze and F. Guattari) and “intrigue” (P. Ricoeur). Their methodological application to the critical analysis and transformation of the living traditions in transitional societies can be called Phenomenological Deconstruction of the Living Tradition.